Induced tensile properties with EB- cross linking of hybridized kenaf/palf reinforced HDPE composite - Aji, Isuwa Suleiman; Zainudin, Edi Syams; Mohd Dahlan, Khairul Zaman; Abdan, Khalina; Salit, Mohd Sapuan (Universiti Putra Malaysia Press, 2013)
Electron beam irradiation, without any addition of cross-linking agents, was investigated at varying doses of EB-Irradiation to develop an environmentally friendly hybridized kenaf (bast)/ pineapple leaf fibre (PALF) bio-composites. Improvement in tensile property of the hybrid was achieved with the result showing a direct proportionality relationship between tensile properties and increasing radiation dose. Statistical analysis software (SAS) was employed to validate the result. HDPE has been shown to have self-cross-linked, enabling interesting tensile properties with irradiation. Statistical analysis validated the results obtained and also showed that adequate mixing of fibres and matrix had taken place at 95% confidence level. Hybridization and subsequent irradiation increased the tensile strength and modulus of HDPE up to 31 and 185%, respectively, at about 100kGy. Meanwhile, SEM was used to view the interaction between the fibres and matrix.